2000
DOI: 10.1007/s002689910004
|View full text |Cite
|
Sign up to set email alerts
|

Altered Bile Composition in the Gallbladder and Common Bile Duct of Patients with Anomalous Pancreaticobiliary Ductal Junction

Abstract: The high incidence of biliary tract carcinoma in patients with anomalous pancreaticobiliary ductal junction (APBDJ) has been well documented. Elevation of the secondary and free bile acid (FBA) concentrations is considered a risk factor for biliary carcinogenesis in these patients. Bile from the gallbladder and common bile duct in 12 patients with APBDJ was analyzed and compared with gallbladder bile from 19 patients with gastric cancer and a normal hepatobiliary tract. The concentrations of secondary bile aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…[1][2][3] PBM is defined as the union of the pancreatic and common bile ducts outside the wall of the duodenum, beyond the influence of the sphincter of Oddi. [3][4][5][6][7] Normally, the pancreaticobiliary duct and junction are governed by sphincter, but as a result of the anomaly, pancreatic juice can reflex into the common bile duct. PBM patients are known to be associated with bile duct dilatation and also biliary tract carcinoma, especially in the Far East.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] PBM is defined as the union of the pancreatic and common bile ducts outside the wall of the duodenum, beyond the influence of the sphincter of Oddi. [3][4][5][6][7] Normally, the pancreaticobiliary duct and junction are governed by sphincter, but as a result of the anomaly, pancreatic juice can reflex into the common bile duct. PBM patients are known to be associated with bile duct dilatation and also biliary tract carcinoma, especially in the Far East.…”
mentioning
confidence: 99%
“…PBM patients are known to be associated with bile duct dilatation and also biliary tract carcinoma, especially in the Far East. [3][4][5][6][7] Patients who develop gallbladder carcinoma in association with PBM are usually 10 years younger than those without PBM. Synchronous primary cancers of the gallbladder and common bile duct have also been associated with PBM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sugiyama [25] had suggested that elevation of the lysolecithin (LL) in the bile was one of the factors for development of biliary tract carcinoma in patients with APBDU: the LL in the phospholipid produced from lecithin by activated phospholipase A 2 in the refluxed pancreatic juice, was significantly elevated in the APBDU group. Yoon [26] also indicated that bile acids induced both EGFR phosphorylation and enhanced COX-2 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteriadegraded bile acids also present in the gastric aspirate from remote postgastrectomy patients though consisting of a small portion of the whole reflux bile acids. Secondly, lysophosphatidylcholine (lysoPC), the product of phosphatidylcholine hydrolysis by phospholipase A2, has been suggested to play a role in the pathogenesis of gallbaldder cancer in the APBDJ (Anomalous Pancreaticobiliary Ductal Junction) patients [47] . LysoPC might also be produced in the stump stomach due to the reflux juice containing aberrant pancreatic juice and bile.…”
Section: Discussionmentioning
confidence: 99%